2017
DOI: 10.1016/j.ejpb.2016.12.029
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated liposomes for topical vaginal therapy improve delivery of interferon alpha

Abstract: Recent studies regarding mucosal drug delivery indicate that nanosystems with surface-available polyethylene glycol (PEG) are able to penetrate mucus barrier, assure closer contact with the epithelium, and improve drug delivery to vagina. In the present work, we developed the mucus-penetrating PEGylated liposomes containing interferon alpha-2b (IFN α-2b), destined to provide localized therapy for human papilloma virus (HPV) vaginal infections. The PEGylated liposomes were of a mean size of 181±8nm, bearing a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 48 publications
(87 reference statements)
1
44
0
1
Order By: Relevance
“…The in vitro polyphenol release studies were performed by using Franz diffusion cells (1.77 cm 2 diffusion area, 12 mL acceptor volume; PermeGear, Bethlehem, PA, USA) [29] equipped with a V6A Stirrer (PermeGear, Bethlehem, PA, USA). The heating circulator (Julabo Laboratechnik, F12-ED, Seelbach, Germany) was set to maintain a temperature of 37 • C. To mimic the vaginal pH [30], the Pharmaceutics 2020, 12, 9 5 of 21 acceptor chambers were filled with phosphate buffer pH 4.5 and ethanol was added at the final concentration of 20% (v/v) [31][32][33] to ensure sink conditions during the study (the solubility of Q and GA in the releasing conditions was found to be 0.226 ± 0.042 mg/mL and 78.7 ± 3.4 mg/mL, respectively).…”
Section: In Vitro Polyphenol Release Studiesmentioning
confidence: 99%
“…The in vitro polyphenol release studies were performed by using Franz diffusion cells (1.77 cm 2 diffusion area, 12 mL acceptor volume; PermeGear, Bethlehem, PA, USA) [29] equipped with a V6A Stirrer (PermeGear, Bethlehem, PA, USA). The heating circulator (Julabo Laboratechnik, F12-ED, Seelbach, Germany) was set to maintain a temperature of 37 • C. To mimic the vaginal pH [30], the Pharmaceutics 2020, 12, 9 5 of 21 acceptor chambers were filled with phosphate buffer pH 4.5 and ethanol was added at the final concentration of 20% (v/v) [31][32][33] to ensure sink conditions during the study (the solubility of Q and GA in the releasing conditions was found to be 0.226 ± 0.042 mg/mL and 78.7 ± 3.4 mg/mL, respectively).…”
Section: In Vitro Polyphenol Release Studiesmentioning
confidence: 99%
“…Recently, Jøraholmen et al prepared PEG‐coated liposomes intended for local delivery of interferon alpha‐2b (IFN α‐2b) to treat vaginal infections of human papilloma virus. Penetration studies performed on the vaginal tissue obtained from pregnant sheep showed elevated IFN α‐2b penetration from PEG‐coated liposomes (≈40% of the drug penetrated) as compared to the unencapsulated IFN α‐2b (≈10% of the drug penetrated).…”
Section: Mucus Penetrationmentioning
confidence: 99%
“…Considering optimal mucus-penetration, a nearly neutral vesicle surface charge is desirable to assure mucus-penetrating properties. 25) Liposomes were nanometer in size in the TEM image and appeared to be homogeneously dispersed. But when the particle size was measured, it was found in micrometer size.…”
Section: )mentioning
confidence: 99%